Talpa altaica Nikolsky 1883 - Russell A. Mittermeier; Don E. Wilson (Lynx Edicions, 2018)
22. Altai Mole Talpa altaica French: Taupe de Sibérie / German: Altai-Maulwurf / Spanish: Topo de Altai Other common names: Siberian Mole Taxonomy. 7 Talpa altaica Nikolsky, 1883, Valley of Tourak, Altai Mountain, Siberia Russian. lalpa altaica is in subgenus Asioscalops, ranked by some authors as a distinct genus. lalpa altaica is the steam species of Talpa. Up to 4-6 subspecies were recognized in the past, but their boundaries are not resolved. Monotypic. Distribution. W & C Siberia, from the Irtysh River Basin E to Baikal region and upper reaches of Lena River Basin, and from Yenisei River at 68-69°30’N S to Altai, Salair, and Sayan Mts, NE Kazakhstan, and NW Mongolia (N Great Lakes Depression and Hovsgol Mts). Descriptive notes. Head-body 124-232 mm, tail 20-34 mm, hindfoot 19-24-6 mm; weight up to 225 g. Males are larger than females. The Altai Mole is the largest species of Talpa, with short tail and broad rhinarium. Eyelids are not sealed; acoustic aperture is I mm in diameter. Furis light mouse gray, blackish gray, or deep brown, with buff tints along spine and on throat and chest. Albino individuals are rare. Pelvis has fourth sacral foramen open posteriorly. Skull differs from other species of Talpa with its extended nares and slit-like anteorbital foramen. Upper tooth row is short, accounting for 35-40% of condylo-basal length. Teeth are small, and upper premolars are nearly as large as upper molars; upper incisor is high and daggerlike; and M' is narrow, with small protocone. Dental formulais13/3,C1/1,P4/4,M 3/3 (x2) = 44. Due to frequent supernumerary, absent, and connate teeth, actual dental formula is between 34 and 47, and 23% of Altai Moles have numbers of teeth that deviate from 44. Missing premolars are the most common anomaly, followed by connate teeth and supernumerary teeth. Habitat. Forest-steppe mosaic, deciduous and mixed forests, southern taiga, and alpine pastures up to elevations of 2000-3500 m. The Altai Mole is widespread in forests with dense cover of grass or shrubs, high ...